Implementasi Pembelajaran Akidah Akhlak Dalam Pembentukan Karakter Religius di SMA Ar Rahman Medan - M. Rizki Setiawan; Tumiran Tumiran (Yayasan Rahmat Islamiyah, 2025)
This study focuses on investigating the implementation of Aqidah Akhlak instruction in shaping religious character at SMA Ar Rahman Medan, identifying its supporting and hindering factors, as well as the resulting outcomes. As a core subject in Islamic education, Aqidah Akhlak makes a substantial contribution to forming students’ behavior, morals, and ethics. Through Aqidah lessons, students are taught firm belief in Allah SWT and the values of faith, while Akhlak lessons guide them to exhibit noble behavior and commendable attitudes in everyday life. The study employs a qualitative approach with a case study method, gathering data through observation, interviews, and documentation. Participants consist of teachers, students, and the principal. The findings reveal that the implementation of Aqidah Akhlak instruction at SMA Ar Rahman Medan significantly shapes students’ character particularly in honesty, responsibility, discipline, and empathy toward others.